"Permen Jasa" (Permen Jahe-Daun Sirsak), Pemanfaatan Kombinasi Pengobatan dari Leluhur sebagai Solusi Alami dalam Pencegahan Penyakit Kardiovaskuler pada Pria dan Pekerja Menggunakan Produk Lokal - Royyan Adiwijaya (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2019)
Minister of Health, Nila F. Moeloek, said that Indonesian men’s life expectancy is only 69 years. This data is worsened by the fact 9 last years of men is sickly age, leaving only 60 years of life span.There are many factors affecting the short age of Indonesian men, one of which is cardiovascular disease.Based on WHO 2012, cardiovascular disease claimed 31% of total world deaths and ¾ of it occurred in developing countries such as Indonesia. This is caused by high in fat, sugar and salt diet. As a result, risk factor for high prevalence of cardiovascular disease in Indonesian men is lifestyle. Of course, public participation would be minimal if they are forced to abandon the famous Indonesian culinary, one of the most delicious in the world. Even so, the problem suffered by these men cannot be ignored.Acaraki, or Nusantara’s ancient pharmacists have found herbs to deal with heart disease and its symptoms using ginger and soursop leaves. Phytochemistry has revealed the efficacy of Gingerol in ginger as a blood thinner, antihyperlipidemia, and antioxidants agent as well as efficacy of soursop as an effective vasodilator. All these properties are packed into herbal candy namely Permen Jasa.